Primary osteosarcoma of the clavicle and the perils of bone biopsy. (24th April 2015) - Cundy, William J; Carter, Christopher; Dhatrak, Deepak; Clayer, Mark
Abstract : We present a rare case of delayed diagnosis of osteosarcoma of the medial clavicle in a young man. He presented following a pathological fracture with a falsely reassuring core and fine-needle aspiration biopsy. The initial biopsy was suggestive of an aneurysmal bone cyst and was therefore treated conservatively without further follow-up. The rapid increase in size over the next 8 months triggered a repeat presentation and subsequent repeat biopsy. The open biopsy confirmed high-grade osteosarcoma and the patient underwent claviculectomy with neoadjuvant chemotherapy.